Pengaruh Kecerdasan Intrapersonal dan Minat Belajar Terhadap Hasil Belajar PAI Siswa Kelas X SMA Negeri 1 Kedunggalar Tahun Ajaran 2021/2022 - Zidni, Kusumaning; Mohammad Ali; Muthoifin (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This research is motivated by the low student learning outcomes in the PAI field at SMA Negeri 1 Kedungalar. Student learning outcomes have many influencing factors, including intelligence factors and student learning interest factors. This study aims to describe intrapersonal intelligence, interest in learning and learning outcomes of PAI at SMK Negeri 1 Kedunggalar. In this study using a quantitative approach. The population of this study were students of class X SMA Negeri 1 Kedunggalar. Data collection techniques using questionnaires and documentation. While the analysis used is multiple regression analysis technique. Research results: 1). There is a significant correlation between intrapersonal intelligence and student learning outcomes in class X SMA Negeri 1 Kedunggalar. Shown at a significance level of 5%, rxy(ro) = 0.354 and rt = 0.232, rxy > rt, then Ho is rejected. It was concluded that the higher the students' intrapersonal intelligence, the higher the PAI learning outcomes. 2). There is a significant correlation between learning interest and learning outcomes of class X students of SMA Negeri 1 Kedunggalar. Indicated by a significance level of 5%, rxy(ro) = 0.403 and rt = 0.232, rxy > rt, then Ho is rejected. It was concluded that the higher the student's learning interest, the higher the PAI learning outcomes. 3). Intrapersonal intelligence and interest in learning have a significant effect on student learning outcomes. This is indicated by a significance level of 5%, where F_count = 9.3019761 and F_table = 3.13, so Fcount > Ftable, so Ho is rejected. Based on the calculation of the coefficient of determination (R2) a value of 21.23643% is obtained, meaning that the variability of the factors of intrapersonal intelligence (x1) and learning interest (x2) has an effect of 21.23643% on PAI learning outcomes (y) and 78.76357%. Keywords: Intrapersonal Intelligence; Interest to learn; PAI learning outcomes